Dr. Dana Aboul Hosn's Quest to Rescue Abandoned Lebanese Dogs - Jaber, Jasmine (The Washington report on Middle East affairs, 2023)
Dr. Dana Aboul Hosn is dedicated to rescuing abandoned dogs in Lebanon. She started by bringing stray and starving dogs home and providing them with medical attention. In 2012, she established her first animal shelter, Angels With Paws, which initially housed 30 dogs but quickly grew to accommodate 150. Tragically, 50 of her dogs were killed when someone threw poison through the shelter's fence. Undeterred, Dr. Dana relocated the shelter to El Qalaa and now cares for over 600 neglected and abandoned dogs. Her efforts also led to the passing of a law in 2017 to protect animals from abuse and mistreatment in Lebanon.